A Theory of Contracts with Limited Enforcement. (9th July 2016) - Martimort, David; Semenov, Aggey; Stole, Lars
Abstract: We develop a theory of contracts with limited enforcement in the context of a dynamic relationship. The seller is privately informed on his persistent cost, while the buyer remains uninformed. Public enforcement relies on remedies for breaches. Private enforcement comes from terminating the relationship. We first characterize enforcement constraints under asymmetric information. Those constraints ensure that parties never breach contracts. In particular, a high-cost seller may be tempted to trade high volumes at high prices at the beginning of the relationship before breaching the contract later on. Such "take-the-money-and-run" strategy becomes less attractive as time passes. It can thus be prevented by backloading payments and increasing volumes over a transitory phase . In a mature phase, enforcement constraints are slack and the optimal contract, although keeping memory of the shadow cost of enforcement constraints binding earlier on, looks stationary. Second-best distortions depend on a modified virtual cost that encapsulates this shadow cost of enforcement.